Professional Development of Business Students: Vision Creating (ENTRENOVA - ENTerprise REsearch InNOVAtion Journal, 2017)
The paper presents the results of our study of management education. We discuss the importance of intrinsic motivation identification and creative exercise that can stimulate inner research of the students. Vision creation is a part of strategic management that is incorporated in the management education as a course material and skill development. Personal reflection was used as a method to identify business students’ vision for their future development. Our study demonstrates positive effects of the vision creation exercise and several different inspirations and role models for the students’ future paths that we elaborate upon and provide future recommendations.This work is licensed under a Creative Commons Attribution-NonCommercial 4.0 International License.